APLIKASI RESTFULL PADA SISTEM INFORMASI GEOGRAFIS PARIWISATA KOTA BANDAR LAMPUNG - Melvitasari Tinambunan; Sanriomi Sintaro (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2021)
Android, Geographic Information Systems, RESTful, Web One of the mapping technologies widely used today is Geographic Information Systems. Geographic Information Systems (GEOGRAPHIC INFORMATION SYSTEMS) is a mapping technology in the form of computer-based information systems, designed to work using data that has spatial information or spatial reference. Mapping technology is widely used to facilitate human work. In this research, Geographic Information System technology was used to support one of the business processes at the Bandar Lampung City Tourism Office. This system was built to assist related agencies in recording tourist sites. The system consists of a web-based system and Android-based applications that are connected using RESTful Web Service. The system is implemented using the PHP programming language with the help of CodeIgniter for web-based systems, and the Java programming language for Android-based applications. The method of developing the system used is the waterfall model method according to Rossa U.S. and Saladin (2014). Application design is based on Unified Modeling Language (UML), flowchart diagrams, and interface design. While the application used in the creation of the Android base system is Android Studio. The testing method used is the system's functional Black-Box. The results of black-box testing data show that the system runs as it should, the system is easy to understand by users, and can meet the functional needs of the system needed by the Bandar Lampung City Tourism Office